Blood bacterial wilt disease of banana: the distribution of pathogen in infected plant, symptoms, and potentiality of diseased tissues as source of infective inoculums - HADIWIYONO HADIWIYONO (Nusantara Bioscience, 2011)
Abstract. Hadiwiyono. 2011. Blood bacterial wilt disease of banana: the distribution of pathogen in infected plant, symptoms, and potentiality of diseased tissues as source of infective inoculums. Nusantara Bioscience 3: 112-117. Bacterial wilt caused by blood disease bacterium (BDB) is the most important disease of banana in Indonesia. The disease was difficult to control due to by poorly understood of ecology and epidemiology of the disease. This paper reports the distribution of pathogen-infected plant, symptoms, and potentiality of diseased tissues as source of inoculums. For studying the distribution of BDB in diseased banana, a number of 14 points of plant organ tissue was sampled and the pathogen was detected by PCR using a couple of specific primer for BDB, 121F, and 121R. In addition to the detection of BDB using PCR, both external and internal symptoms were observed. All the points of detection were also used as source of inoculums to search the potentiality of the tissues as source of infective inoculums. The results showed that BDB was distributed systemically in infected banana. The pathogen infection caused systemic symptom and all part of infected banana were potential as source of infective inoculums.